Pengaruh Kepemimpinan dan Komunikasi Terhadap Efektivitas Kerja Pegawai - Ayesa Putri Renisa; Azhara Fetri Stevana (CV. ITTC INDONESIA, 2025)
This article discusses the influence of leadership and communication on employee work effectiveness. The author uses a literature review approach to provide readers with an understanding of how these two factors are related to employee performance. Work effectiveness is defined as the degree to which organizational goals are achieved through the activities carried out. Several factors contribute to this effectiveness, including leadership and communication. Leadership and communication are understood as the ability of an individual to encourage, guide, direct, or influence others or a group to accept certain ideas or policies in order to achieve predetermined goals. Therefore, it can be concluded that leadership and communication play a crucial role in improving employee performance and supporting the organization's success in achieving its objectives.